Mapping of exogenous choline uptake and metabolism in rat glioblastoma using deuterium metabolic imaging (DMI) - Ip, Kevan L.; Thomas, Monique A.; Behar, Kevin L.; de Graaf, Robin A.; De Feyter, Henk M. (Frontiers in Cellular Neuroscience, 2023)
Introduction: There is a lack of robust metabolic imaging techniques that can be routinely applied to characterize lesions in patients with brain tumors. Here we explore in an animal model of glioblastoma the feasibility to detect uptake and metabolism of deuterated choline and describe the tumor-to-brain image contrast. Methods: RG2 cells were incubated with choline and the level of intracellular choline and its metabolites measured in cell extracts using high resolution 1H NMR. In rats with orthotopically implanted RG2 tumors deuterium metabolic imaging (DMI) was applied in vivo during, as well as one day after, intravenous infusion of 2H9-choline. In parallel experiments, RG2-bearing rats were infused with [1,1’,2,2’-2H4]-choline and tissue metabolite extracts analyzed with high resolution 2H NMR to identify molecule-specific 2H-labeling in choline and its metabolites. Results: In vitro experiments indicated high uptake and fast phosphorylation of exogenous choline in RG2 cells. In vivo DMI studies revealed a high signal from the 2H-labeled pool of choline+metabolites (total choline, 2H-tCho) in the tumor lesion but not in normal brain. Quantitative DMI-based metabolic maps of 2H-tCho showed high tumor-to-brain image contrast in maps acquired both during, and 24 hours after deuterated choline infusion. High resolution 2H NMR revealed that DMI data acquired during 2H-choline infusion consists of free choline and phosphocholine, while the data acquired 24 hours later represent phosphocholine and glycerophosphocholine. Discussion: Uptake and metabolism of exogenous choline was high in RG2 tumors compared to normal brain, resulting in high tumor-to-brain image contrast on DMI-based metabolic maps. By varying the timing of DMI data acquisition relative to the start of the deuterated choline infusion, the metabolic maps can be weighted towards detection of choline uptake or choline metabolism. These proof-of-principle experiments highlight the potential of using deuterated choline combined with DMI to metabolically characterize brain tumors.